Cover Feature: Optically Active Polyoxometalate‐Based Silica Nanohelices: Induced Chirality from Inorganic Nanohelices to Achiral POM Clusters (Chem. Eur. J. 44/2018). Issue 44 (26th July 2018) - Attoui, Mariam; Pouget, Emilie; Oda, Reiko; Talaga, David; Le Bourdon, Gwénaëlle; Buffeteau, Thierry; Nlate, Sylvain
Abstract : Chiral Polyoxometalate Nanohelices have been prepared by chiral arrangement of non‐chiral polyoxometalate (POM) clusters onto silica nanohelices as chiral sources. The induced chirality from silica nanohelices to POM clusters is stable, resulting in robust and easy to handle chiral NANOPOM helices. More information can be found in the Full Paper by S. Nlate, T. Buffeteau, et al. onpage 11344 .